Penetapan Harga Dan Penguasaan Pasar Oleh Transportasi Online Dalam Perspektif Hukum Persaingan Usaha - Aprilia Stefany Leliak; Gusti Ferdiany Sriwardan; Savina Ayu Maharani (Batulis Civil Law Review, 2021)
Starting in 2014, the online transportation appeared, the vehicles used by this transportation are also different from other conventional transportation. People who are accustomed to using conventional transportation can switch their interests due to cheaper fares and a more practical ordering system, namely through online applications. The chaos of online transportation stems from accusations that its presence is considered illegal because it does not meet the implementation of public transportation. The most basic thing is that initially online transportation did not have an Indonesian legal entity, did not have a public transportation business, and there was no obligation to conduct a due diligence (KIR). As a result, online transportation does not pay taxes, so online taxis are able to offer cheaper fares. Thus, it is necessary to study further regarding the rules regarding the determination of online transportation fares in Indonesia. Then there is a further study regarding indications of unfair business competition with online transportation fares. As a result, online transportation does not pay taxes, so online taxis are able to offer cheaper fares.